PHYTOCHEMICAL PROFILE, ANTIOXIDANT AND ANTIDIABETIC POTENTIAL OF ESSENTIAL OIL FROM FRESH AND DRIED LEAVES OF EUCALYPTUS GLOBULUS - Lamidi Ajao Usman (Journal of the Chilean Chemical Society, 2022)
Pathogenesis of type 2 diabetes has been linked to oxidative stress. Synthetic drugs in use for the management of the stress and type 2 diabetes are expensive and their usage are associated with side effects. Some essential oils exhibited antioxidant and antidiabetic properties devoid of the effects. Their activities are attributed to the type of phytochemicals whose presence in the oils of the fresh and dried samples are determined by environmental factors.  This study therefore aimed at monitoring the effect of air-drying at ambient temperature on the phytochemical profile, antidiabetic and antioxidant potentials of leaf essential oils of E.globulus. To achieve this, 500 g of fresh and dried leaves of E. globuluswere separately pulverized and hydrodistilled for three hours. The leaves yielded oils in the range of 0.22–0.55% (w/w). GC and GC–MS analyses of the oils revealed predominance of α-phellandrene (4.6–10.5%), D-limonene (18.5%) , β-myrcene (20.8%), m-cymene (5.0-29.8%), terpinen-4-ol (0.4-4.7%), globulol (3.1-10.5%) and spathulenol (4.9-18.8%). The antioxidant activity of the oils was determined by DPPH and FRAP assays using ascorbic acid as standard. α-Amylase and α-glucosidase inhibitory assays were used to determine the antidiabetic potential of the oils using acarbose as standard. The oils exhibited antioxidant and antidiabetic activities that compared favourably with the standards. Meanwhile, the oil obtained from the leaves air-dried for three days showed the highest activities with competitive mode of α-amylase and α-glucosidase inhibitions. The oil could serve as alternative for the management of oxidative stress and type 2 diabetes.